2007
DOI: 10.1677/joe-06-0122
|View full text |Cite
|
Sign up to set email alerts
|

Functional specificity of the rainbow trout (Oncorhynchus mykiss) gonadotropin receptors as assayed in a mammalian cell line

Abstract: In vertebrates, gonadotropins (GTHs) (FSH and LH) are two circulating pituitary glycoprotein hormones that play a major role in the regulation of gonadal functions, including gonadal cell proliferation/differentiation and steroidogenesis. In mammals, it is well known that their biological effects are mediated by highly specific membrane-bound receptors expressed preferentially on the somatic cells of the gonads. However, in fish, binding and functional studies have shown that cross-reactivity may occur in GTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 57 publications
4
34
0
1
Order By: Relevance
“…This observation is consistent with the fact that in trout, Fsh and Lh activate preferentially their cognate receptor at the concentration used here (Sambroni et al 2007). Among the genes preferentially regulated by Fsh, we found the transcripts that were previously shown to be expressed in the Sertoli cells, such as amh in fish (Skaar et al 2011) and Wisp1, Abca1, Smtn, Krt18, Slc40a1, Col1a1, Ccnd1, and Fstl3 in mice (Chalmel et al 2007).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This observation is consistent with the fact that in trout, Fsh and Lh activate preferentially their cognate receptor at the concentration used here (Sambroni et al 2007). Among the genes preferentially regulated by Fsh, we found the transcripts that were previously shown to be expressed in the Sertoli cells, such as amh in fish (Skaar et al 2011) and Wisp1, Abca1, Smtn, Krt18, Slc40a1, Col1a1, Ccnd1, and Fstl3 in mice (Chalmel et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Besides, in fish, one could hypothesize that both gonadotropins activate the same receptor type in the target cells. However, as mentioned above, such promiscuous action of Lh on Fsh receptor activity appears unlikely because we previously showed that trout gonadotropins used at 500 ng/ml did not crossactivate their reciprocal receptor (Sambroni et al 2007). Finally, the common effects of the gonadotropins could, at least in part, be mediated through indirect actions resulting from the stimulation of sexual steroids.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…4, B expression steadily increases during testicular maturation, while in sea bass and rainbow trout, 388 according to Sambroni et al(2007), LHR mRNA levels were maintained almost constant until 389 the end of the recrudescence stage. Analysis of LH levels in sea bass plasma (Fig.…”
Section: Correlation Analysis 334mentioning
confidence: 99%